Design of a welding table as a medium for determining elbow points and joints - Afiff Yudha Tripariyanto; Lolyka Dewi I; Ana Komari; Johan Aalfian (LPPMPK-Sekolah Tinggi Teknologi Muhammadiyah Cileungsi, 2024)
Welding is a method of joining two or more metals with electrode extension media using current heating and voltage according to the variation in the thickness of the iron material used. Welding is one of the connection media with a patent system, meaning that the results of the process can be changed by damaging the results of the welding process. From looking at several welding workshops, almost all of them to do welding are under or on the ground so many workers complain that they tend to be more tired and the welding results are less than optimal, especially for symmetrical or straightness of the connection results. The method used in this research is to design a welding table that is adjusted to the level of needs, especially for the height of the table and the centric axis to combine so that the results of the connection process are completely straight and reduce the results of welding defects. The purpose of designing this welding table is to use it as a method for working on the welding process so that the welding results are really strong and straight according to the design drawing. From the results of the design process, a welding table is obtained with iron material as a table base to place the workpiece to be cut. using borders of iron with a thickness of approximately 120 x 240 x 40cm using Material: Iron plate about 5-6 mm thick. In addition, the results of the design process also reduce the welding process time for blunt joints from 85 seconds to 48 seconds, overlap joints from 85 seconds to 60 seconds, and T joints from 88 seconds to 81 seconds. The quality of the welding results is visually better, the results of welding defects are smaller and straighter or symmetrical